Oxygen Exchange Kinetics of SrTiO3 Single Crystals: A Non‐Destructive, Quantitative Method. Issue 6 (15th March 2018) - Stöber, Max; Cherkouk, Charaf; Leisegang, Tilmann; Schelter, Matthias; Zosel, Jens; Walter, Juliane; Hanzig, Juliane; Zschornak, Matthias; Prucnal, Slawomir; Böttger, Roman; Meyer, Dirk C.
Abstract: The time‐resolved oxygen exchange rate of strontium titanate (SrTiO3 ) single crystals is studied by means of oxygen solid electrolyte coulometry (OSEC) and compared to model calculations. Experiments are performed on pure, ion implanted (Ni, Ag, O and N ions) and partially covered crystals with silver layer. In this work, a theoretical model is used, which is based on defect chemistry under equilibrium conditions. It is applied as a fit in order to determine the effective rate constants and activation energy of the oxygen exchange reaction on the crystal surface. OSEC is used for the first time to characterize kinetic parameters of oxygen exchange on single crystalline surfaces. Transmission electron microscopy and sputter X‐ray photoelectron spectroscopy are performed to determine structural and chemical changes after ion implantation. Abstract : The time‐resolved oxygen exchange rate of strontium titanate (SrTiO3 ) single crystals is studied by means of oxygen solid electrolyte coulometry and compared to model calculations. Experiments are performed on pure, ion implanted (Ni, Ag, O and N ions) and partially covered crystals with silver layer. The kinetic parameters of oxygen exchange on single crystalline surfaces where obtained from the model calculations.